2017
DOI: 10.3233/bmr-169622
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of kinesio taping applied in patients with knee osteoarthritis: A randomized controlled trial

Abstract: In conclusion, we could report that kinesio taping has significant immediate effects after a single kinesio taping application on range of motion, pain and functional status in patients with knee osteoarthritis. We could also report that KT in addition to conventional treatment is not superior to conventional treatment alone in terms of clinical outcomes over 3 weeks later.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
37
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 29 publications
1
37
1
Order By: Relevance
“…In detail, in both the first research group [16] found that KT users had an amelioration in pain compared to the control group. In the latter [17], where groups were additionally sorted according to the tension/no tension application, a similar result was found. KT has an effect on other pain-related disorders, such as osteoarthritis (OA).…”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…In detail, in both the first research group [16] found that KT users had an amelioration in pain compared to the control group. In the latter [17], where groups were additionally sorted according to the tension/no tension application, a similar result was found. KT has an effect on other pain-related disorders, such as osteoarthritis (OA).…”
Section: Introductionsupporting
confidence: 70%
“…However, other schools do not share the same application technique [10,14]. KT may not be capable of instantaneously modifying strength production in healthy players, but could have an important positive result on muscle fatigue resistance during frequent concentric muscle actions [14][15][16][17]. Additionally, the potential beneficial effects of KT on muscle endurance should not be ignored either [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 which an important role in maintaining the stability and function of the knee joint. 8,23 The quadriceps femoris muscle can perform several functions on the knee with isometric, eccentric and concentric activation. Through isometric activation, the quadriceps femoris femoris muscle stabilizes and helps protect the knee joint.…”
mentioning
confidence: 99%
“…Through isometric activation, the quadriceps femoris femoris muscle stabilizes and helps protect the knee joint. 23 Eccentric activation provides the benefit of "shock absorption" in the knee. The quadriceps femoris muscle helps reduce the impact of loading/impact loading on the knee by functioning as a spring, thus a strong quadriceps femoris muscle can protect knee joint, decrease pain and improve role of the patients.…”
mentioning
confidence: 99%